2007
DOI: 10.2106/jbjs.f.01002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Manual and Gravity Stress Radiographs for the Evaluation of Supination-External Rotation Fibular Fractures

Abstract: The gravity stress radiograph is equivalent to the manual stress radiograph for determining deltoid ligament injury in association with an isolated distal fibular fracture, and thus it can be used to determine ankle stability in patients who present with an isolated distal fibular fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 25 publications
0
87
0
Order By: Relevance
“…An overview is shown in Tables 1 and 2. Three trails investigated medial tenderness [12,16,29]; two studies, ecchymosis [16,29]; two studies, swelling [16,29]; one study, an injury radiograph [46]; six studies, a type of radiographic stress view [12,16,18,29,32,35,45]; one study, the Lauge-Hansen classiWcation [46]; one study, MRI [24]; and one article studied arthroscopy [46] in the evaluation of the deltoid ligament integrity. The publication dates span 6 years; in 2001, Michelson et al [32] was the earliest and in 2007, Koval et al [24] and Schock et al [45] were the most recent publications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An overview is shown in Tables 1 and 2. Three trails investigated medial tenderness [12,16,29]; two studies, ecchymosis [16,29]; two studies, swelling [16,29]; one study, an injury radiograph [46]; six studies, a type of radiographic stress view [12,16,18,29,32,35,45]; one study, the Lauge-Hansen classiWcation [46]; one study, MRI [24]; and one article studied arthroscopy [46] in the evaluation of the deltoid ligament integrity. The publication dates span 6 years; in 2001, Michelson et al [32] was the earliest and in 2007, Koval et al [24] and Schock et al [45] were the most recent publications.…”
Section: Resultsmentioning
confidence: 99%
“…Tornetta stated that these tests are the gold standard of subluxation, an indirect measurement of deltoid injury or deltoid insuYciency. The amount of medial clear space widening indicative of a positive external rotation stress or gravity-stress test has been somewhat variable in the literature [8,12,16,18,19,21,23,28,29,32,35,40,46]. Normal values reported in the literature have varied from 1 to 5 mm [8,11,19,21,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Evaluation of the medial clear space (MCS) in these bimalleolar equivalent injuries on stress radiographs has shown that American Orthopaedic Foot and Ankle Society Ankle and Hindfoot Functional Survey scores decline with an increase in MCS 11 when treated conservatively.…”
Section: Pankovich and Shivarammentioning
confidence: 99%